The INSPIRESat-1: Mission, science, and engineering. Issue 6 (15th September 2021) - Chandran, Amal; Fang, Tzu-Wei; Chang, Loren; Hari, Priyadarshan; Woods, Thomas N.; Chao, Chi-Kuang; Kohnert, Richard; Verma, Ankit; Boyajian, Spencer; Duann, Yi; Evonosky, William; Kompella, Mallikarjun; et al.
Abstract: INSPIRESat-1 (IS-1) is a small scientific satellite being developed jointly by the Laboratory for Atmospheric and Space Physics (LASP) at the University of Colorado at Boulder in the United States, the Indian Institute of Space Science and Technology (IIST) in India, the National Central University (NCU) in Taiwan and the Nanyang Technological University (NTU) in Singapore. This paper describes the science objectives of the IS-1 mission, the engineering and current development status. The IS-1 has completed all functional and performance tests as well as all environmental tests. The spacecraft is manifested on the Indian Space Research Organization's (ISRO) Polar Satellite Launch Vehicle (PSLV) C-52 mission in 2021. The IS-1 carries two scientific instruments: the Compact Ionospheric Probe (CIP) developed at NCU for studying Earth's dynamic ionosphere and the Dual-zone Aperture X-ray Solar Spectrometer (DAXSS) developed at LASP for studying the highly-variable solar X-ray radiation. It also carries a Command and Data Handling board developed by IIST. The primary science objectives of the INSPIRESat-1 are twofold. First, using CIP to characterize the temporal and spatial distributions of small-scale plasma irregularities like plasma bubbles in the ionosphere. Secondly, IS-1 aims to provide a greater understanding of why the Sun's corona is orders of magnitude hotter than the photosphere, why there is an abundance of elements change during different solar events, and how these events (observed with greater soft x-ray fidelity) affect the earth's ionosphere. The International Satellite Program in Research and Education (INSPIRE) is a consortium of universities with active space programs, formed to advance space science and engineering.